Resisting dominant language and literacy ideologies through family multilingualism and the making of ikhaya - Molate, Babalwayashe (School of Education, 2025)
Multilingualism is a social practice that humans have negotiated and managed uninhibited, long before the understanding of ‘language policy' as regulating mechanism with its oppressive monoglossic language ideologies (Romaine, 2001) came into being. As a consequence of occupation and division of African regions into colonies, monolingual ideologies that favoured European languages while marginalising African languages were passed along, thus denying the heteroglossic nature of African multilingualism (Makalela, 2018). Against the backdrop of this tension of interactions between monoglossia and heteroglossia, I examine family discourses in everyday language use of a South African family. In this family, processes of attribution of value to linguistic forms and practices are inscribed together with the construction of social difference and social inequality with which they are associated (Heller, 2007). Drawing on language socialisation (Schieffelin & Ochs, 1986) and epistemologies of the south (Escobar, 2016) as theoretical frameworks, this study examines language and literacy practices and ideologies of an African-language(s) speaking family with a child who attends an historically white, English-medium school in South Africa. Using linguistic ethnography and digital ethnography, I constructed and analysed the case of an isiXhosa speaking mother-child duo as focal participants, who traverse between their township and rural homes, thus challenging Western notions of household arrangement and ‘nuclear/extended' family. Further, reflecting on the making of family and the variety of language registers and literacy practices observed offered insights into how the complex, fluid and dynamic structure of family mirrors the same complexity in heteroglossic language practices. With this insight, I introduce the term ikhaya, the isiXhosa word denoting both family and home, and expand on the definition of ‘family' in the African context. I argue that ikhaya captures the domain of home that is distributed across multiple physical homesteads and geographical spaces, as well as family, showing how language and home literacy practices in digital and physical spaces are pivotal in constructing family and resisting dominant language ideologies.